A spatial-temporal gated attention module for molecular property prediction based on molecular geometry. Issue 5 (5th April 2021) - Li, Chunyan; Wang, Jianmin; Niu, Zhangming; Yao, Junfeng; Zeng, Xiangxiang
Abstract: Motivation: Geometry-based properties and characteristics of drug molecules play an important role in drug development for virtual screening in computational chemistry. The 3D characteristics of molecules largely determine the properties of the drug and the binding characteristics of the target. However, most of the previous studies focused on 1D or 2D molecular descriptors while ignoring the 3D topological structure, thereby degrading the performance of molecule-related prediction. Because it is very time-consuming to use dynamics to simulate molecular 3D conformer, we aim to use machine learning to represent 3D molecules by using the generated 3D molecular coordinates from the 2D structure. Results: We proposed Drug3D-Net, a novel deep neural network architecture based on the spatial geometric structure of molecules for predicting molecular properties. It is grid-based 3D convolutional neural network with spatial-temporal gated attention module, which can extract the geometric features for molecular prediction tasks in the process of convolution. The effectiveness of Drug3D-Net is verified on the public molecular datasets. Compared with other deep learning methods, Drug3D-Net shows superior performance in predicting molecular properties and biochemical activities. Availability and implementation: https://github.com/anny0316/Drug3D-Net Supplementary Data: Supplementary data are available online at https://academic.oup.com/bib .